Why Do Customers Still Use Telemedicine Platforms? Analysis During the COVID-19 Endemic in Solo, Indonesia - Mangruwa, Rajiv; Syahputra, Syahputra (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
The COVID-19 pandemic has changed people's lifestyles as they adapt to the 'new normal' situation. One significant change is the widespread use of telemedicine. Hallodoc is one the largest telemedicine platforms in Indonesia and is the 1st he choice of many patients in developing learning skills amidst the post-COVID-19 pandemic. The Solo City became the sample and the best city in Indonesia's 2023 Investment Services Award. This research uses the SOR approach to determine consumer behavior's influence on consumer purchasing decisions for Halodoc products in the post-pandemic period, with Situations and Objects as Stimuli, Consumers as Organisms, and Purchasing Decisions as the response. This research uses a quantitative method with a survey approach by distributing questionnaires to 100 respondents who are Solo residents who have used Halodoc products in the post-pandemic period. The analysis method uses SEM-PLS. This research found that from the five hypotheses studied, it can be concluded that consumer behavior positively and significantly influences consumer purchasing decisions for Halodoc services.